PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI ULANG YANG DI MEDIASI OLEH KEPUASAN PELANGGAN PADA PRODUK TEH CELUP MEREK 2 TANG DI KOTA BANDUNG - Pratama, Rizky; Abdul Ahmad Hafid Nurmansyah (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The aim of this research is to examine the effect of product quality on repurchase intention which is mediated by customer satisfaction of filtered tea drink in the 2 Tang brand packaging in the city of Bandung. The instrument in this research has been declared to have passed the validity test and reliability test. This instrument was used as a data collection tool from respondents aged 16 years and over who had consumed the 2 Tang brand of filtered tea drink, which was the object assessed in this study, as many as 119 people. The data collection technique used was convenience sampling which is included in non-probability sampling. The data analysis technique used is multiple linear regression using SPSS version 26 tools and using a Sobel test calculator. Of the four research hypotheses proposed, all are supported by empirical data. The findings of this research show that customer satisfaction can mediate the influence of product quality on repurchase intention. The results of this research are also useful for the management of the object being assessed and the similar food and beverage industry regarding designing strategies that are relevant to improving the quality of these attributes